Driving Excellence In Customer Experience: A Comparative Study Of Quality Management Tactics In Public Enterprise, Government Bodies, and The Hospitality Industry - Jaya, Arman; Ramadhani, Hanif Fariz; Istikarani , Miranda; Prabowo , Yogi Muhammad Pandu; Charles, Ricardo; Fitri, Aisyah Farah Yasira (SEAN Institute, 2024)
This research delves into the quality management approaches within a state-owned enterprise, a government organization, and the hospitality industry to discern their influence on customer satisfaction. Utilizing a descriptive-qualitative method, the study garners data through meticulous field observation, informant interviews, and extensive documentation. The findings reveal that each company has adopted and tailored quality management practices to suit their operations, leading to enhanced customer satisfaction. Despite this progress, the research identifies significant challenges, notably in human resource competence, which could impede customer satisfaction. Each entity, however, has devised strategic solutions to these challenges, fostering the advancement of their quality management systems. The study contributes to the discourse on quality management, offering stakeholders a lens to augment their strategies. It recognizes the limitations posed by the scope of data collection and calls for future research to delve deeper, ensuring a more comprehensive understanding of the practices and their outcomes.